Analysis Of Business Model Canvas And Integration Of Islamic Values In The 10k Breakfast Business - Rozalina Rozalina; Dhelvita Sari; Udin Saripudin; Tasya Aspiranti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The low rate of breakfast consumption in Indonesia, especially among students and workers, due to factors such as time and budget constraints, creates business opportunities for practical and affordable breakfast solutions. Sarapan 10K responds to this need, but its operations are not yet based on a systematic business model framework. This study aims to analyze the application of the Business Model Canvas (BMC) and examine the integration of Islamic values in the business practices of Sarapan 10K to understand the strengths, weaknesses, and opportunities for business development. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with business managers, observations, and document analysis, then analyzed thematically based on the nine BMC blocks. The results show that Sarapan 10K has built a strong value proposition based on affordability, completeness, and halal certification, as well as serving a diverse customer segment. However, weaknesses were found in revenue stream diversification, digital channel and ordering platform optimization, and dependence on a cost structure that is vulnerable to fluctuations. On the other hand, this business has integrated Islamic business principles such as justice, tauhid, khilafah, ma'ad, nubuwwah, which are manifested through amanah, shidiq, fathanah, and tabligh, as well as social responsibility. The study recommends diversifying revenue, utilizing social media, and strengthening Sharia-based 10K Breakfast MSME Partners through zakat, coaching programs, and profit-sharing systems to improve competitiveness and sustainability.